Ultrahigh-toughness marble-imitated ultrahigh-performance concrete and preparation method thereof

By using metakaolin and ultrasonic mechanical vibration technology in UHPC, the problem of uneven dispersion of nanocellulose fibers in UHPC is solved, the flexural strength and toughness are improved, and high-performance imitation marble concrete is realized, suitable for white building decoration Material.

CN119263747AInactive Publication Date: 2025-01-07河南省第二建设集团有限公司

Patent Information

Application Number
CN202411804782.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When using nano-scale cellulose fibers, existing UHPCs are difficult to disperse evenly, affecting performance, especially in white concrete, and have insufficient compressive strength, which cannot meet the requirements of ultra-high performance.

Method used

Metakaolin is used as a coordinated dispersion matrix, combined with ultrasonic mechanical vibration and magnetic stirring technology to form a nanocellulose-metakaolin dispersed suspension to ensure that it is evenly dispersed in UHPC, plays a bridge role, and improves flexural strength and toughness.

Benefits of technology

It significantly improves the flexural strength and toughness of UHPC, reduces self-shrinkage, has good crack resistance, has no pores on the surface, has better performance than natural marble, and is economical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263747A_ABST
    Figure CN119263747A_ABST
Patent Text Reader

Abstract

The invention relates to the field of building materials, and particularly discloses ultra-high-toughness marble-imitated ultra-high-performance concrete and a preparation method thereof. According to the prepared ultra-high-performance concrete with ultra-high toughness, marble-imitated material and white system, the metakaolin is used as a synergistic dispersion matrix, the nano-scale cellulose fibers are fully dispersed in the matrix, the performance advantages of the nano-scale cellulose fibers can be fully played through the method, the agglomeration problem of nano-scale cellulose is solved, and the super-high-performance concrete with the ultra-high toughness, marble-imitated material and white system is obtained. The homogeneity of the concrete is improved. The bridging effect of the nanoscale cellulose fibers is more effectively exerted, so that the breaking strength and the toughness of the ultra-high performance concrete are greatly improved. The used synergistic dispersion metakaolin is white, the color of the concrete is not influenced after the metakaolin is doped, the prepared concrete is highly similar to marble, and the surface of the concrete is free of pores and defects. The application can effectively supplement application deficiency of a white ultra-high performance concrete synergistic dispersion system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to an ultra-high-toughness marble-like ultra-high-performance concrete and a preparation method thereof. Background Art

[0002] In the prior art, although the use of nano-scale cellulose fibers in UHPC can enhance various performances of UHPC, it will greatly reduce the workability of UHPC. In addition, due to its poor solubility in water, it is not easy to disperse evenly, affecting homogeneity and having poor use effect. The general synergistic dispersion technology often uses cement and silica fume as synergistic dispersants, but cement and silica fume are generally dark in color and difficult to be applied to white concrete.

[0003] Among building decoration materials, marble is relatively common and looks beautiful after processing. However, it is expensive and relatively soft and easy to scratch. In view of this, how to give full play to the toughening and shrinkage reduction effects of nano-cellulose fibers in white UHPC and make them evenly dispersed without precipitation is of great significance to broaden the scope of use of UHPC and achieve the effect of imitating marble.

[0004] Publication Nos. CN 106396555 B and CN 116903320 A respectively disclose methods for preparing concrete with the addition of nanocellulose. However, the first item only mentions the addition of nanocellulose during mixing of the mixture. Since nanocellulose itself is insoluble in water, it is difficult to evenly distribute it in the concrete by directly adding it to the mixture. Agglomeration will occur during the mixing process, affecting the workability of the mixture. In addition, the uneven distribution of nanocellulose is not conducive to the bridging effect, and will affect the local hydration process, indirectly inhibiting the growth of strength. The second disclosure has the same problem, and the maximum compressive strength of the concrete material produced can only reach 50MPa, which does not belong to the category of UHPC.

[0005] In view of the above problems, the present invention adopts a synergistic dispersion technology with a metakaolin solution as a dispersion matrix. As a highly active mineral admixture, metakaolin can be hydrated to contribute to the overall strength of concrete, and its finer particle size can entrain nanocellulose particles. The mechanical vibration generated by ultrasound in the liquid can destroy the structure of molecules in the liquid and particles in the solid, causing them to lose their stable state and form smaller particles. When ultrasound acts on larger particles in the liquid, the energy density of the particles increases, and the primary particles will produce mechanical vibrations, which will eventually lead to particle crushing and dispersion. The high frequency of ultrasound can quickly and evenly crush and disperse particles, and has high efficiency that conventional stirring and dispersion methods cannot match. Through the synergistic treatment method of magnetic stirring + ultrasonic dispersion, a metakaolin-nanocellulose dispersion suspension can be formed, and then added to the stirring of UHPC in liquid form to ensure that it is evenly dispersed and not agglomerated, and better play a bridging role for the matrix, while not affecting the working performance of the UHPC mixture. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present application provides an ultra-high toughness imitation marble ultra-high performance concrete and a preparation method thereof. The imitation marble UHPC prepared by the concrete has the corresponding advantages of general marble slabs, and has strong compression resistance, tensile resistance, wear resistance, and corrosion resistance, and has high economic efficiency. It is a new type of building decoration material worthy of promotion.

[0007] The present application provides an ultra-high toughness marble-like ultra-high performance concrete, wherein the concrete comprises cement, metakaolin, white silica fume, quartz sand, water, steel fiber, water reducing agent, defoaming agent and nano-scale cellulose fiber.

[0008] Furthermore, in parts by mass, the cement is 950-1100 parts, the metakaolin is 150-200 parts, the white silica fume is 0-150 parts, the quartz sand is 1000-1400 parts, the steel fiber is 100-400 parts, the water reducer is 40-80 parts, the water is 189-270 parts, the defoamer is 1-3 parts, and the nano-cellulose fiber is 0.5-5 parts.

[0009] Furthermore, the cement is PO 52.5 white cement with a whiteness of ≥85; the specific surface area of ​​the metakaolin is ≥15m 2 / g, whiteness ≥90; the specific surface area of ​​the white silica fume ≥12 m 2 / g, whiteness ≥90.

[0010] Furthermore, the quartz sand particles range from 0.106 to 0.212 mm; the water reducer is a polycarboxylic acid water reducer; and the steel fiber has a length of ≥12 mm and a diameter of ≤0.2 mm.

[0011] Furthermore, the nano-scale cellulose fibers are CNF carboxylated cellulose nanofibers, which have a diameter of 3-12 nm, a length of 0.5-3 μm, and a carboxyl content of 1.2-3 mmol / g.

[0012] The present invention provides a method for preparing the above-mentioned ultra-high toughness marble-like ultra-high performance concrete, which is prepared by the following steps: S1: Take out all the mass of nano-cellulose fibers required for preparing the concrete, mix with part of the metakaolin and water, and the mixing ratio is 6:150-200:1000-1500; metakaolin is used as a synergistic dispersion matrix, and the nano-cellulose fibers are fully dispersed in the matrix. Through this method, the performance advantages of nano-cellulose fibers can be fully utilized, the agglomeration problem of nano-cellulose can be solved, and the homogeneity of concrete can be improved. The "bridging" role of nano-cellulose fibers can be more effectively exerted, thereby greatly improving the flexural strength and toughness of ultra-high performance concrete.

[0013] S2: Put the mixed solution obtained in step S1 into a magnetic stirrer and stir for 10 minutes to form a preliminary stirring to form a mixed solution; S3: After being stirred by a magnetic stirrer, the entire mixed solution was taken out, placed in an ultrasonic disperser, and stirred at a power of 800 W for 10-20 minutes to obtain a synergistic dispersion; S4: adding the synergistic dispersion treated in step S3 into a concrete mixer, and adding the remaining cement, water, metakaolin, white silica fume, and quartz sand into the concrete mixer and stirring for 2-3 minutes until a plastic cement-based slurry is formed; S5: gradually add steel fiber into the concrete mixer, adding about 10% of the total amount of steel fiber each time, and continue to add steel fiber until all steel fiber is added after no steel fiber is visible on the visible surface of the mixer; S6: After adding the last batch of steel fibers, continue stirring for about 1 minute, take out the concrete and pour it into the mold.

[0014] S7: After one day of curing at room temperature, demould and check the apparent color difference and the presence of pores.

[0015] The present invention also provides an imitation marble slab made of the above-mentioned ultra-high toughness imitation marble ultra-high performance concrete. Beneficial Effects

[0016] (1) This application uses kaolin as a co-dispersing matrix and fully disperses nano-cellulose fibers in the matrix. Through this method, the performance advantages of nano-cellulose fibers can be fully utilized, the agglomeration problem of nano-cellulose can be solved, and the homogeneity of concrete can be improved. The "bridging" effect of nano-cellulose fibers can be more effectively exerted, thereby greatly improving the flexural strength and toughness of ultra-high performance concrete. The co-dispersing agent kaolin used is white, and does not affect the color of the concrete after being added. The prepared concrete is highly similar to marble, and there are no pores or defects on the surface. This application can effectively supplement the lack of application of white ultra-high performance concrete co-dispersing system.

[0017] (2) The flexural strength of UHPC prepared by using nanocellulose fiber-kaolin synergistic dispersion technology is increased by more than 40% compared with ordinary UHPC, which greatly improves the toughness of UHPC. Its shrinkage is reduced by more than 30% compared with ordinary UHPC, and it has good crack resistance and is not prone to warping deformation.

[0018] (3) The imitation marble slab made of concrete prepared by the present invention has a color and texture similar to marble, is dense and has no pores on the surface. However, its strength, impact resistance, corrosion resistance and other properties are much better than those of natural marble. It is natural, environmentally friendly and has a long service life, which complies with the dual carbon policy. Materials such as connectors can be embedded in advance without destroying the integrity of the material, thereby increasing the scope of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A preparation flow chart of ultra-high toughness marble-like ultra-high performance concrete DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] An embodiment of the present application: an ultra-high toughness marble-like ultra-high performance concrete, the raw materials of which include: cement, kaolin, white silica fume, quartz sand, steel fiber, water reducer, water, defoamer, and nano-cellulose fiber.

[0022] Furthermore, the cement is PO 52.5 white cement with a whiteness of ≥85; the specific surface area of ​​the metakaolin is ≥15m 2 / g, whiteness ≥90; the specific surface area of ​​the white silica fume ≥12 m 2 / g, whiteness ≥90. The quartz sand particle range is 0.106-0.212mm; the water reducer is a polycarboxylic acid water reducer; the steel fiber length is ≥12mm, and the diameter is ≤0.2mm. The nano-scale cellulose fiber is CNF carboxylated cellulose nanofiber, with a diameter of 3-12 nm, a length of 0.5-3 μm, and a carboxyl content of 1.2-3 mmol / g.

[0023] The method for preparing the ultra-high-toughness marble-like ultra-high performance concrete described in the present invention is prepared by the following steps: S1: Take out all the mass of nano-cellulose fibers required for preparing the concrete, mix with part of the metakaolin and water, use the metakaolin as a coordinated dispersion matrix, and fully disperse the nano-cellulose fibers in the matrix. Through this method, the performance advantages of nano-cellulose fibers can be fully utilized, the agglomeration problem of nano-cellulose can be solved, and the homogeneity of concrete can be improved. The "bridging" role of nano-cellulose fibers can be more effectively exerted, thereby greatly improving the flexural strength and toughness of ultra-high performance concrete.

[0024] S2: Put the mixed solution obtained in step S1 into a magnetic stirrer and stir for 10 minutes to form a preliminary stirring to form a mixed solution; S3: After being stirred by a magnetic stirrer, the entire mixed solution was taken out, placed in an ultrasonic disperser, and stirred at a power of 800 W for 10-20 minutes to obtain a synergistic dispersion; S4: adding the synergistic dispersion treated in step S3 into a concrete mixer, and adding the remaining cement, water, metakaolin, white silica fume, and quartz sand into the concrete mixer and stirring for 2-3 minutes until a plastic cement-based slurry is formed; S5: gradually add steel fiber into the concrete mixer, adding about 10% of the total amount of steel fiber each time, and continue to add steel fiber until all steel fiber is added after no steel fiber is visible on the visible surface of the mixer; S6: After adding the last batch of steel fibers, continue stirring for about 1 minute, take out the concrete and pour it into the mold.

[0025] S7: After one day of curing at room temperature, demould and check the apparent color difference and the presence of pores.

[0026] The present invention also provides an embodiment: an imitation marble slab made of the above-mentioned ultra-high toughness imitation marble ultra-high performance concrete.

[0027] The UHPC prepared by the nanocellulose fiber-metakaolin synergistic dispersion technology in this application has a flexural strength that is more than 40% higher than that of ordinary UHPC, greatly improving the toughness of UHPC. Its shrinkage is more than 30% lower than that of ordinary UHPC, and it has good crack resistance and is not prone to warping. The imitation marble UHPC prepared by this concrete has the corresponding advantages of ordinary marble slabs, and has strong compression, tensile, wear and corrosion resistance, and is highly economical. Example 1

[0028] A method for preparing ultra-high toughness marble-like ultra-high performance concrete, the raw materials include 1016 parts of cement, 191 parts of metakaolin, 67 parts of white silica fume, 1020 parts of quartz sand, 156 parts of steel fiber, 50 parts of water reducer, 171 parts of water, 1 part of defoamer, and 2.5 parts of nano-cellulose fiber. The above-mentioned method for preparing ultra-high toughness marble-like ultra-high performance concrete is prepared by the following steps: S1: taking out all the mass of nano-scale cellulose fibers required for preparing the concrete, and mixing them with part of the metakaolin and water, with the mixing ratio being 6:150-200:1000-1500; S2: Put the mixed solution obtained in step S1 into a magnetic stirrer and stir for 10 minutes to form a preliminary stirring to form a mixed solution; S3: After being stirred by a magnetic stirrer, the entire mixed solution was taken out, placed in an ultrasonic disperser, and stirred at a power of 800 W for 10-20 minutes to obtain a synergistic dispersion; S4: adding the synergistic dispersion treated in step S3 into a concrete mixer, and adding the remaining cement, water, metakaolin, white silica fume, and quartz sand into the concrete mixer and stirring for 2-3 minutes until a plastic cement-based slurry is formed; S5: gradually add steel fiber into the concrete mixer, adding about 10% of the total amount of steel fiber each time, and continue to add steel fiber until all steel fiber is added after no steel fiber is visible on the visible surface of the mixer; S6: After adding the last batch of steel fibers, continue stirring for about 1 minute, take out the concrete and pour it into the mold.

[0029] S7: After one day of curing at room temperature, demould and check the apparent color difference and the presence of pores. Example 2

[0030] An ultra-high toughness marble-like ultra-high performance concrete, the raw materials include 1056 parts of cement, 130 parts of metakaolin, 130 parts of white silica fume, 1316 parts of quartz sand, 156 parts of steel fiber, 60 parts of water reducer, 156 parts of water, 1 part of defoamer, and 3 parts of nano-cellulose fiber. The other steps are the same as those in Example 1. Comparative Example 1

[0031] An ultra-high performance concrete, the raw materials include 1016 parts of cement, 191 parts of metakaolin, 67 parts of white silica fume, 1020 parts of quartz sand, 156 parts of steel fiber, 50 parts of water reducer, 171 parts of water, and 1 part of defoamer. Except that the nano-cellulose fiber is not added, the other steps are the same as those in Example 1. Comparative Example 2

[0032] An ultra-high performance concrete, wherein the raw materials include 1056 parts of cement, 130 parts of kaolin, 130 parts of white silica fume, 1316 parts of quartz sand, 156 parts of steel fiber, 60 parts of water reducer, 156 parts of water, and 1 part of defoamer, except that nano-cellulose fiber is not added, the other steps are the same as those in Example 2.

[0033] The performance tests were carried out on each embodiment, wherein the flexural strength was measured after 28 days of standard curing, and the method was referred to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The autogenous shrinkage test method of concrete was referred to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009). The results are shown in Table 1.

[0034] Table 1

[0035] From the results of Examples 1 and 2, it can be found that compared with Comparative Examples 1 and 2, the synergistic dispersion of metakaolin-nano-cellulose fibers can greatly improve the flexural strength of UHPC and reduce the autogenous shrinkage of UHPC. The reason is that the addition of synergistically dispersed nano-cellulose fibers makes the nano-cellulose fibers more evenly dispersed and the bridging effect more obvious. Compared with Example 1, within the scope of this application, Example 2 has a higher cellulose fiber dosage, so the bridging effect is more obvious and the performance improvement is increased. In Examples 1 and 2, the added nano-cellulose fibers have less precipitation and more effective ingredients, so the pore structure is optimized and the autogenous shrinkage of UHPC is reduced.

[0036] In summary, the UHPC prepared by the nanocellulose fiber-metakaolin synergistic dispersion technology in this application has a flexural strength increased by more than 40% compared with ordinary UHPC, greatly improving the toughness of UHPC. Its autogenous shrinkage is reduced by more than 30% compared with ordinary UHPC, and it has good crack resistance and is not prone to warping. The imitation marble UHPC prepared by this concrete has the corresponding advantages of ordinary marble slabs, and has strong compression, tensile, wear and corrosion resistance, and has high economy. It is a new type of building decoration material worthy of promotion.

[0037] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An ultra-high toughness marble-like ultra-high performance concrete, characterized in that: The concrete comprises cement, metakaolin, white silica fume, quartz sand, water, steel fiber, water reducing agent, defoaming agent and nano-scale cellulose fiber.

2. The ultra-high toughness marble-like ultra-high performance concrete according to claim 1, characterized in that: In parts by mass, the cement is 950-1100 parts, the metakaolin is 150-200 parts, the white silica fume is 0-150 parts, the quartz sand is 1000-1400 parts, the steel fiber is 100-400 parts, the water reducer is 40-80 parts, the water is 189-270 parts, the defoamer is 1-3 parts, and the nano-cellulose fiber is 0.5-5 parts.

3. The ultra-high toughness marble-like ultra-high performance concrete according to claim 2, characterized in that: The cement is PO 52.5 white cement with a whiteness of ≥85; the specific surface area of ​​the metakaolin is ≥15 m 2 / g, whiteness ≥90; the specific surface area of ​​the white silica fume ≥12 m 2 / g, whiteness ≥90.

4. The ultra-high toughness marble-like ultra-high performance concrete as claimed in claim 3, characterized in that: The quartz sand particles range from 0.106 to 0.212 mm; the water reducer is a polycarboxylic acid water reducer; the steel fiber has a length of ≥12 mm and a diameter of ≤0.2 mm.

5. The ultra-high toughness marble-like ultra-high performance concrete according to claim 4, characterized in that: The nano-scale cellulose fibers are CNF carboxylated cellulose nano-fibers, which have a diameter of 3-12 nm, a length of 0.5-3 μm, and a carboxyl content of 1.2-3 mmol / g.

6. A method for preparing ultra-high toughness marble-like ultra-high performance concrete according to any one of claims 1 to 5, characterized in that: Prepared by the following steps: S1: taking out all the mass of nano-scale cellulose fibers required for preparing the concrete, and mixing them with part of the metakaolin and water, with the mixing ratio being 6:150-200:1000-1500; S2: Put the mixed solution obtained in step S1 into a magnetic stirrer and stir for 10 minutes to form a preliminary stirring to form a mixed solution; S3: After being stirred by a magnetic stirrer, the entire mixed solution was taken out, placed in an ultrasonic disperser, and stirred at a power of 800 W for 10-20 minutes to obtain a synergistic dispersion; S4: adding the synergistic dispersion treated in step S3 into a concrete mixer, and adding the remaining cement, water, metakaolin, white silica fume, and quartz sand into the concrete mixer and stirring for 2-3 minutes until a plastic cement-based slurry is formed; S5: gradually add steel fiber into the concrete mixer, adding 10% of the total amount of steel fiber each time, and continue to add steel fiber until all steel fiber is added after no steel fiber is visible on the visible surface of the mixer; S6: After the last batch of steel fibers is added, stirring is continued for 1 minute, and the concrete is taken out and poured into the mold; S7: After one day of curing at room temperature, demould and check the apparent color difference and the presence of pores.

7. A marble-like slab, characterized in that: It is made of the ultra-high toughness marble-like ultra-high performance concrete described in any one of claims 1-5.

Citation Information

Patent Citations

  • An ultra-high performance cement-based composite material based on cellulose fiber internal curing and its preparation method

    CN106396555B

  • Coarse-aggregate-containing C240-strength-grade ultrahigh-performance fiber concrete and preparation method

    CN107285708A

  • Modified toughening material for well cementation

    CN112174568A

  • Steel fiber cement-based composite material based on nanoscale reinforcement and preparation method thereof

    CN113072343A

  • Nanofiber-doped cement mortar test piece composite material and preparation method thereof

    CN116903320A

Cited By

  • Novel UHPC material for bridge expansion joints and preparation method thereof

    CN120962857A